Multiplicity Results to a Conformable Fractional Differential Equations Involving Integral Boundary Condition - Shuman Meng; Yujun Cui (Complexity)
In this article, by using topological degree theory couple with the method of lower and upper solutions, we study the existence of at least three solutions to Riemann-Stieltjes integral initial value problem of the type Dαx(t)=f(t,x),  t∈[0,1], x(0)=∫01x(t)dA(t), where Dαx(t) is the standard conformable fractional derivative of order α, 0<α≤1, and f∈C([0,1]×R,R). Simultaneously, the fixed point theorem for set-valued increasing operator is applied when considering the given problem.